3D Soil Structure Interaction Effects on the Seismic Behavior of Single Span Historical Masonry Bridge - Ozmen, Alper; Sayin, Erkut (Springer, 2023)
Historical masonry bridges are cultural heritage of countries and must be protected from destructive effects of nature such as earthquakes, floods, and fires. The interaction of soil and structure has a significant impact on the seismic behavior of masonry bridges. In this study, the effect of Soil-Structure Interaction (SSI) was investigated on a single-span masonry bridge using non-linear time-history analysis. A SSI model of the Velipalas masonry bridge and soil layer was created using 3D solid elements in DIANA software. The nonlinear behavior of the masonry units and soil layer was modeled using the total strain-based crack model and Mohr-Coulomb failure criteria. The earthquakes of 1992 Erzincan, 2003 Bingol, and 2020 Sivrice were used for earthquake excitation. Results showed that considering SSI increased the periods, displacements, velocities, and principal stresses, but reduced the frequency and acceleration values. Hence, the results indicate that SSI effects are significant for the seismic response of single-span masonry bridges.
Keywords: Finite element method; Soil-structure interaction (SSI); Masonry arch bridge; Time history analyses; Seismic response; Nonlinear analyses